Analisis Yuridis Tindak Pidana Penggelapan Mobil Rental dengan Identitas Palsu: Studi Putusan PN Palu No. 180/Pid.B/2023/PN Pal - Amri Siregar; Halimatul Maryani (Albayan Journal of Islam and Muslim Societies, 2024)
The phenomenon of car rental embezzlement using false identities has emerged as a growing form of crime in line with the increasing demand for rental-based transportation services. This crime not only causes significant financial losses to rental business owners but also raises complex legal issues, involving elements of fraud and identity misuse. This article provides a juridical analysis of the District Court of Palu Decision No. 180/Pid.B/2023/PN Pal, which adjudicated a case of car rental embezzlement using a false identity, employing a normative juridical approach with an emphasis on both substantive and procedural criminal law. The findings highlight the implications of applying Article 372 of the Indonesian Penal Code (KUHP) on embezzlement in relation to Article 263 on forgery. This study contributes to the literature on legal protection for car rental businesses and offers insights into the development of criminal law in addressing new forms of crime.